Neurofibromin 1 mutations impair the function of human induced pluripotent stem cell-derived microglia - Kuhrt, Leonard D.; Motta, Edyta; Elmadany, Nirmeen; Weidling, Hannah; Fritsche-Guenther, Raphaela; Efe, Ibrahim E.; Cobb, Olivia; Chatterjee, Jit; Boggs, Lucy G.; Schnauß, Marina; Diecke, Sebastian; Semtner, Marcus; et al. (Disease models & mechanisms, 2023)
Neurofibromatosis type 1 (NF1) is an autosomal dominant condition caused by germline mutations in the neurofibromin 1 (NF1) gene. Children with NF1 are prone to the development of multiple nervous system abnormalities, including autism and brain tumors, which could reflect the effect of NF1 mutation on microglia function. Using heterozygous Nf1-mutant mice, we previously demonstrated that impaired purinergic signaling underlies deficits in microglia process extension and phagocytosis in situ. To determine whether these abnormalities are also observed in human microglia in the setting of NF1, we leveraged an engineered isogenic series of human induced pluripotent stem cells to generate human microglia-like (hiMGL) cells heterozygous for three different NF1 gene mutations found in patients with NF1. Whereas all NF1-mutant and isogenic control hiMGL cells expressed classical microglia markers and exhibited similar transcriptomes and cytokine/chemokine release profiles, only NF1-mutant hiMGL cells had defects in P2X receptor activation, phagocytosis and motility. Taken together, these findings indicate that heterozygous NF1 mutations impair a subset of the functional properties of human microglia, which could contribute to the neurological abnormalities seen in children with NF1.
Gesehen am 09.09.2024